2005
DOI: 10.1074/jbc.m504963200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible Factor Prolyl 4-Hydroxylase Inhibition

Abstract: Hypoxia-inducible factor (HIF) prolyl 4-hydroxylases are a family of iron-and 2-oxoglutarate-dependent dioxygenases that negatively regulate the stability of several proteins that have established roles in adaptation to hypoxic or oxidative stress. These proteins include the transcriptional activators HIF-1␣ and HIF-2␣. The ability of the inhibitors of HIF prolyl 4-hydroxylases to stabilize proteins involved in adaptation in neurons and to prevent neuronal injury remains unclear. We reported that structurally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(97 citation statements)
references
References 60 publications
2
89
0
Order By: Relevance
“…Activation of HIF-1␣ also promotes the survival and progression of various cancers (29,30). In contrast, it has beneficial effects on ischemic injury to the heart and brain, suggesting that a low molecular weight activa- tor of HIF-1␣ and its target genes could provide a novel treatment for stroke and myocardial infarction (31,32). The beneficial effects of HIF-1 are mostly mediated by its target genes, the most prominent of which are EPO and VEGF, which are considered major mediators of the protective effect of hypoxic preconditioning (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of HIF-1␣ also promotes the survival and progression of various cancers (29,30). In contrast, it has beneficial effects on ischemic injury to the heart and brain, suggesting that a low molecular weight activa- tor of HIF-1␣ and its target genes could provide a novel treatment for stroke and myocardial infarction (31,32). The beneficial effects of HIF-1 are mostly mediated by its target genes, the most prominent of which are EPO and VEGF, which are considered major mediators of the protective effect of hypoxic preconditioning (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Prolyl hydroxylases are iron-dependent enzymes that reduce levels of HIFs via their ability to hydroxylate these proteins, marking them for subsequent degradation by the ubiquitinproteasome system. Reduction in HIF signaling pathways by PHDs results in decreased transcription of several genes whose protein products have been shown to be protective against either oxygen depletion or oxidative stress within the brain (10,44,45). Because PHDs require the presence of iron, it is possible that iron chelation therapy is in part protective against MPTP neurotoxicity by resulting in decreased PHD activity, which can contribute to the induction of protective HIF-dependent genes including those involved in cellular iron regulation and protection against oxidative stress and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…PHD inhibitors have been demonstrated to prevent oxidative cell death and ischemic injury via HIF pathway activation (10). More recently, it has been shown that inactivation of HIF-1␣ in specific cortical and striatal neurons exacerbated tissue damage in a mouse model of ischemia (11).…”
Section: Parkinson Disease (Pd)mentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Furthermore, it was reported that a hypoxic environment and the function of HIFs are important for the maintenance of neuronal undifferentiation and proliferation, 13,14 and that hypoxic preconditioning or pharmacological HIF activation may suppress pathological phenotypes of experimental retinal degeneration and cerebral infarction. 15,16 Based on this background, we hypothesized that constitutive HIF activation may protect the retina from various disease states. Consequently, we undertook the generation of a mouse line that lacks the von Hippel-Lindau gene (Vhl, a negative regulator of HIFs) specifically in the retinal neuron.…”
Section: Introductionmentioning
confidence: 99%